Bibliometric Analysis: Improving the Clinical Skills of Nursing Students through Tutorial-Based Laboratory Learning - Husni; Yusran Hasymi; Eko Risdianto (Journal of Pedagogy and Education Science, 2026)
Recent advancements in nursing education have led to a shift in the paradigm from teacher-centered learning to experiential and reflective learning models. Tutorial-Based Laboratory Learning (TBLL) has emerged as an innovative approach to enhance nursing students’ clinical competence by integrating reflection, problem-solving, and simulation-based practice. This bibliometric study aims to map global research trends, conceptual structures, and thematic evolution in studies focusing on improving nursing students’ clinical skills through TBLL between 2015 and 2025. It also identifies the leading authors, institutions, journals, and countries that contribute to this field. A total of 48 articles were retrieved from the Scopus database and analyzed using VOSviewer 1.6.20 and Biblioshiny (R Studio) to visualize publication trends, keyword co-occurrence, co-authorship, and citation networks. The analysis followed descriptive, conceptual, and evolutionary approaches to illustrate global research patterns.  Findings reveal an increasing trend in publications, peaking in 2021, with Nurse Education Today as the most influential journal. Dominant themes include problem-based learning, critical thinking, self-efficacy, and nursing education. The United States, Turkey, and Australia lead global contributions, reflecting broad international engagement. Key influential contributions were identified through citation network analysis, with several highly cited studies shaping the core knowledge base of TBLL-related clinical skills research. The study highlights TBLL as a transformative pedagogical model that integrates cognitive, affective, and psychomotor learning dimensions. This research contributes to nursing science by providing an evidence-based roadmap for curriculum innovation, reflective evaluation, and simulation-based clinical education in 21st-century nursing programs.